PENGARUH MOTIVASI KEPALA BADAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI BADAN PUSAT STATISTIK KABUPATEN CIREBON - Atik Sridani Wismayanti; Nurudin Siraj; Sri Wulandari (Universitas Swadaya Gunung Jati, 2016)
ABSTRACT The research that the writer did was the Effect of Motivation by the Head of the Agency on Employee Productivity at the Cirebon Regency Central Statistics Agency. The research method that I do is a quantitative research method, which starts with data collection, data interpretation, until the results of the research use numbers.The problem that the author pointed out is that the work productivity of employees at the Cirebon Regency Central Bureau of Statistics has not been maximized, it is suspected that the problem is caused by the lack of optimal motivation implementation by the head of the Cirebon Regency Central Statistics Agency.The research question that the writer proposes is the influence of motivation by the head of the body on employee work productivity. The hypothesis that the authors propose is as follows: